Inward and Outward Spillovers in the SACU Area - Canales Kriljenko, Jorge (IMF Working Papers; Working Paper ;, 2013)
Spillovers from South Africa into the other members of the Souther Africa Customs Union (known as the BLNS for Botstwana, Lesotho, Namibia, and Swaziland) are substantial reflecting sizeable real and financial interlinkages. However, shocks to real GDP growth in South Africa do not seem to systematically affect growth developments in BLNS countries as a group. Nevertheless, vector autoregressions, which allow country-specific parameters, suggest some strong spillovers onto the smaller economies.